Β-methasone-containing biodegradable poly(lactide-co-glycolide) acid microspheres for intraarticular injection: effect of formulation parameters on characteristics and in vitro release. (October 2013) - Song, Xia; Song, San-Kong; Zhao, Pei; Wei, Li-Ming; Jiao, Hai-Sheng
<x xml:space="preserve">Abstract</x> A sustained drug release system based on the injectable poly(lactic-co-glycolic acid) (PLGA) microspheres loaded with β-methasone was prepared for localized treatment of rheumatic arthritis. The microscopy and structure of microspheres were characterized by scanning electron microscope (SEM) and Fourier transform infrared (FTIR). The effects of various formulation parameters on the properties of microspheres and in vitro release pattern of β-methasone were also investigated. The results demonstrated that increase in drug/polymer ratio led to increased particle size as well as drug release rate. Increase in PLGA concentration led to increased particle size, but decreased burst release. The drug encapsulation efficiency increased sharply by increasing polyvinyl alcohol (PVA) concentration in the aqueous phase from 1.5 to 2.0%. β-methasone release rate decreased considerately with decreasing OP (organic phase)/AP (aqueous phase) volume ratio. Stirring rate had significantly influence on the particle size and encapsulation efficiency. Independent of formulation parameters, β-methasone was slowly released from the PLGA microspheres over 11 days. The drug release profile of high drug loaded microspheres agree with Higuchi equation with a release mechanism of diffusion and erosion, that of middle drug loaded microspheres best agreed with Hixcon-Crowell equation and controlled by diffusion and erosion as well. The low drug loaded microspheres well fitted to logarithm normal distribution equation with mechanism of purely Fickian diffusion.